The Casual Labor Problem in Indian Manufacturing - James, Ralph C. (Quarterly Journal of Economics, 1960)
I. Introduction, 100. — II. Labor supply instability, some Indian-American comparisons, 101; turnover, 101; absenteeism, 103; the casual labor problem, 104; “decasualization” as a possible solution, 106. — III. Eliminating the casual labor market for cotton textile workers in Bombay city, 108; the casual labor problem in the 1920's, 108; the employer's approach: mill decasualization (1930's), 108; the government's scheme for industry decasualization (1950's), 109; the belief in corruption which no longer exists, 112. — IV. A recapitulation, 113. — V. Policy implications of the Bombay approach, 114.